Resilience of Protective Coating for Gabions Wire in Harsh Field Conditions - Mohd Yusoff, Nurul Sofiyyah; Chan, Chee-Ming (Penerbit UTHM, 2020)
The stability of earth retaining structures has become a serious problem in many countries. When the slopes are subjected to nature forces such as wind, water and earth movement, their stability can be greatly affected. These can create unstable slopes and increase the potential of slopes failure. Gabion wall is essentially a semi rigid structure that can generally accommodate large lateral and vertical movements without excessive structural distress [1]. The advantages of gabion structure may be cited as durability, flexibility and permeability. Other than that, gabions are considered as cheaper than other conventional process in terms of material and labour.